Identification of a novel aminoglycoside O-nucleotidyltransferase AadA33 in Providencia vermicola - Feng, Chunlin; Gao, Mengdi; Jiang, Weiyan; Shi, Weina; Li, Anqi; Liu, Shuang; Zhang, Lei; Zhang, Xueya; Li, Qiaoling; Lin, Hailong; Lu, Junwan; Li, Kewei; et al. (Frontiers in Microbiology, 2022)
A novel chromosome-encoded aminoglycoside O-nucleotidyltransferase AadA33 was identified in Providencia vermicola strain P13. The AadA33 shares the highest amino acid identity of 51.28% with the function characterized AadA31. Antibiotic susceptibility testing and enzyme kinetics analysis revealed that the function of AadA33 is to mediate spectinomycin and streptomycin resistance. The recombinant strain harboring aadA33 (pUCP20-aadA33/Escherichia coli DH5α) displayed >256- and 128-fold increases in the minimum inhibitory concentration levels to spectinomycin and streptomycin, respectively, compared with the control strains pUCP20/DH5α. Enzyme kinetic parameters manifested the substrate of AadA33 including spectinomycin and streptomycin, with kcat/Km of 3.28 × 104 (M−1 s−1) and 3.37 × 104 (M−1 s−1), respectively. Bioinformatics analysis revealed its structural mechanism of antimicrobial resistance, genetic context, and phylogenetic relationship with other aminoglycoside O-nucleotidyltransferases. This study of AadA33 contributed to understanding the function and resistance mechanism of aminoglycoside O-nucleotidyltransferase.